К вопросу о заимствованиях в современных языках - Лебедева, И. В.; Лебедева, Л. К.
Данная статья рассматривает заимствования в современном языке как вполне логичное явление, присущее каждому языку в разные периоды. Особое внимание уделяется новейшим заимствованиям. Авторы приводят примеры заимствований не только в русском языке, внимание уделяется также особенностям заимствований в немецком и даже новейшим тенденциям поведения таких слов. Авторы также обращают свое внимание и на заимствования в английском языке. This article considers the borrowing in the modern language as a quite logical phenomenon inherent to each language in different periods. Particular attention is paid to the latest borrowings. The authors provide examples of borrowings not only in the Russian language, the attention is paid to the peculiarities of borrowings in the German and even the latest trends in the behavior of such words. The authors are also paying their attention to the borrowings in English.
Keywords: Лингвистика